Digital twin software provider: key players, rankings and trends - Sommer, Lutz (International Journal of Advances in Applied Sciences, 2025)
Current studies about digital twins (DT) generally provide little support to interested parties in selecting suitable providers. The aim of the present study is, on the one hand, to ask whether existing rankings could be used to derive a quick, cost-efficient decision. On the other hand, it is to be questioned how the provider market is developing. Therefore, the study based on the one hand on 10 provider rankings of DT and the other hand on detailed research of n=153 providers was included for a detailed analysis of trends. The following findings were obtained: i) The selected top 10 rankings can serve as a fast, cost-efficient selection approach for providers; ii) the DT market is dominated by established, large top providers with North American locations; and iii) Since 2010 there has been a trend in the form of a disproportionately large number of new providers.